Bioactive food as dietary interventions for diabetes - Watson, Ronald R. (Ronald Ross); Preedy, Victor R. (Bioactive foods in chronic disease states., 2013)
Focuses on the role of bioactive foods in addressing pre-diabetes symptoms, their potential to complement other treatments for those suffering from diabetes and diabetic-related obesity and other health issues. Documents foods that can affect metabolic syndrome and ways the associated information could be used to understand other diseases that share common etiological pathways. Includes insights from experts from around the world, providing global perspectives and options based on various regional foods.